Sodium-zinc-aluminum-nickel-manganese-oxygen layered oxide, preparation method thereof and sodium ion battery

By using sodium zinc aluminum nickel manganese oxide as the positive electrode material of sodium ion battery, the phase transition and performance decay of existing materials in the high voltage zone are solved, and stable electrochemical performance and good rate performance are achieved.

CN119786554AActive Publication Date: 2025-04-08UNIV OF SCI & TECH OF CHINA
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411875801.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-04-08
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

Existing sodium ion battery positive electrode materials are prone to phase transition and irreversible anionic redox reactions in high voltage zones, resulting in electrochemical performance decay and structural collapse.

Method used

Sodium zinc aluminum nickel manganese oxygen layered oxide Na0.70~0.72Zn0.05Al0.05Ni0.28Mn0.62O2 is used as the positive electrode material. This material forms a composite oxide layer with oxygen to improve structural stability.

Benefits of technology

The stable high current cycle performance and good rate performance of the positive electrode material of sodium ion battery are achieved, and phase transition and performance decay in the high voltage zone are avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005197043020000011
    Figure HDA0005197043020000011
  • Figure HDA0005197043020000012
    Figure HDA0005197043020000012
  • Figure HDA0005197043020000021
    Figure HDA0005197043020000021
Patent Text Reader

Abstract

The invention provides a sodium-zinc-aluminum-nickel-manganese-oxygen layered oxide which is shown as a formula of Na (0.70 to 0.72), Zn (0.05), Al (0.05), Ni (0.28) and Mn (0.62) O2. The invention also provides a preparation method of the sodium-zinc-aluminum-nickel-manganese-oxygen layered oxide, which comprises the following steps: S1) mixing the raw materials with the chelating agent according to the proportioning relation to obtain a mixed solution; s2) heating the mixed solution until gel is formed; and S3) sintering the gel to obtain the sodium-zinc-aluminum-nickel-manganese oxide layered oxide. The sodium-zinc-aluminum-nickel-manganese-oxygen layered oxide provided by the invention is used as a positive electrode material of a sodium-ion battery, relatively high specific capacity, working voltage and excellent cycling stability are realized, and when the sodium-zinc-aluminum-nickel-manganese-oxygen layered oxide is used in the sodium-ion battery, the battery has stable large-current cycling performance and better electrochemical structure stability, and the performance of the sodium-ion battery is improved. The method is high in practical application value and can be used for energy storage equipment such as portable electronic devices, energy storage power supplies and communication base stations.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sodium ion batteries, and in particular to a sodium-zinc-aluminum-nickel-manganese-oxygen layered oxide, a preparation method thereof and a sodium ion battery. Background Art

[0002] In recent years, due to the rapid development of portable electronic devices, electric vehicles and hybrid vehicles, the research on energy storage materials with abundant resources, high energy efficiency and environmental friendliness has become an international research hotspot. In order to meet the huge market demand, battery materials cannot be measured only by battery performance. Battery safety, manufacturing cost, energy consumption and environmental friendliness are also included as important indicators for evaluating battery materials. At present, the development prospects of lithium-ion batteries are relatively bright. However, due to the uneven distribution of lithium resources and price restrictions, excessive demand for lithium resources is bound to lead to shortages.

[0003] The research and development of sodium-ion batteries is mainly to solve the contradiction between the huge demand for power batteries and the scarcity of lithium resources. In addition, in addition to lithium, lithium-ion batteries also need to use another rare metal-cobalt; however, with the growth of market demand for power batteries, scarce energy sources such as lithium and cobalt will inevitably face resource depletion and price increases. Sodium, as the second lightest alkali metal element after lithium, has an abundance of 2.3% to 2.8%, which is 4 to 5 orders of magnitude higher than lithium. When lithium resources are facing depletion, sodium-ion batteries will be expected to replace them.

[0004] Research on sodium-ion batteries started almost at the same time as lithium-ion batteries, but with the successful commercialization of lithium-ion batteries, research on sodium-ion batteries has gradually faded. In addition, sodium-ion batteries have significantly different requirements for material lattices than lithium-ion batteries, especially for positive electrode materials, which makes the plan of directly applying materials successfully used in lithium-ion batteries to sodium-ion batteries almost always end in failure. In recent years, researchers have designed materials based on the particularity of sodium-ion batteries and have achieved many breakthrough results, making sodium-ion batteries a research hotspot again.

[0005] For sodium-ion batteries, research on cathode materials is crucial. Cathode materials are not only a key factor in improving the performance of sodium-ion batteries, but also a major bottleneck limiting the cost of sodium-ion batteries. It is urgent to find cathode materials with high specific capacity, high operating voltage, stable structure, low cost, environmental friendliness and good safety.

[0006] According to the crystal structure, the positive electrode materials of sodium ion batteries can be divided into three types: layered materials, polyanion materials and Prussian blue materials. Among them, layered materials have attracted much attention due to their high electronic conductivity and stable layered structure. The general formula of layered oxide positive electrode materials is Na xTMO2 (TM stands for transition metal). In 1980, Delmas et al. divided layered oxides into different structures such as O3, O2, P3 and P2 according to the coordination configuration of sodium ions and the stacking mode of oxygen in MO6 polyhedrons. The capital letters represent the coordination configuration of sodium ions, and the numbers represent the number of stacking layers of the minimum repeating unit of oxygen. Due to the differences in structure, there are also large differences in the electrochemical properties of the corresponding materials. Among them, P2-type materials have wider sodium ion transmission channels and lower sodium ion migration energy barriers, showing faster diffusion kinetics, but their initial capacity is low, and phase transitions between P2 and O2 phases are prone to occur under high pressure, which affects the cycle stability. Compared with P2-type materials, O3-type materials have a higher sodium ion content, thus having a higher initial capacity, but their rate performance and capacity retention are poor.

[0007] In order to solve a series of problems existing in the above-mentioned layered oxide materials, researchers have developed a variety of modification methods. By designing and optimizing the material components, structure and surface, they can improve the specific capacity of the material, enhance the structural stability and air stability of the material, and thus explore the application value of the layered oxide positive electrode.

[0008] Sodium ion layered oxide cathode materials (Na x As a homologue of lithium-ion layered materials (such as LiCoO2), TMO2 has attracted extensive attention and research due to its advantages such as high energy density, low cost and simple synthesis. + radius and strong interlayer electrostatic repulsion, resulting in Na x TMO2 undergoes complex structural transformations during the charge and discharge process, which further affects the electrochemical performance. On the other hand, the energy density of the layered cathode is limited by the content of variable-valence transition metal ions. In order to obtain higher energy density, the layered oxide cathode usually needs to be charged to a high voltage region to activate the oxygen ion redox reaction (>4.0V vs. Na + / Na), by removing more sodium ions to obtain a higher discharge capacity. However, layered cathodes will experience severe phase transitions and irreversible anion redox reactions in the high voltage region, which ultimately lead to electrochemical performance degradation and structural collapse. In order to solve the above problems, the rational design of high-voltage layered materials to obtain high energy density batteries is the focus of current research. Summary of the invention

[0009] The technical problem solved by the present invention is a kind of Na 0.70~0.72 Zn 0.05 Al 0.05 Ni 0.28 Mn 0.62The sodium-zinc-aluminum-nickel-manganese-oxygen layered oxide shown in O2, the layered oxide provided in the present application has a stable electrochemical structure, and as a positive electrode material for a sodium ion battery, has stable high current cycle performance and good rate performance.

[0010] In view of this, the present application provides a sodium zinc aluminum nickel manganese oxide layered oxide as shown in formula (I),

[0011] Na 0.70~0.72 Zn 0.05 Al 0.05 Ni 0.28 Mn 0.62 O2 (Ⅰ).

[0012] Preferably, the layered oxide is composed of several layers of composite oxide and sodium atoms, and the sodium atoms are distributed between two layers of composite oxide; oxygen in the composite oxide forms a bond with zinc, aluminum, manganese and nickel, and oxygen atoms are distributed on the surface of the zinc, aluminum, manganese and nickel.

[0013] Preferably, the size of the layered oxide is 3 to 5 μm.

[0014] The present application also provides a method for preparing the sodium-zinc-aluminum-nickel-manganese-oxygen layered oxide, comprising the following steps:

[0015] S1) mixing a sodium source compound, a zinc source compound, an aluminum source compound, a manganese source compound, and a nickel source compound with a chelating agent according to a ratio to obtain a mixed solution;

[0016] S2) heating the mixed solution until a gel is formed;

[0017] S3) sintering the gel at 100-200° C., 400-600° C. and ≥950° C. in sequence to obtain sodium zinc aluminum nickel manganese oxygen layered oxide.

[0018] Preferably, the sodium source compound is selected from at least one of sodium nitrate and sodium acetate; the zinc source compound is selected from at least one of zinc nitrate and zinc acetate; the aluminum source compound is selected from aluminum nitrate; the manganese source compound is selected from at least one of manganese nitrate and manganese acetate; the nickel source compound is selected from at least one of nickel nitrate and nickel acetate; and the chelating agent is selected from citric acid monohydrate.

[0019] Preferably, the molar ratio of the sodium source compound, the zinc source compound, the aluminum source compound, the nickel source compound, the manganese source compound and the chelating agent is (0.72-0.75): 0.05: 0.05: 0.28: 0.62: 2.26.

[0020] Preferably, the sintering temperatures are 130-180° C., 420-480° C., and 950-1100° C., respectively; and the sintering times are 5-10 h, 5-10 h, or 10-15 h, respectively.

[0021] The present application also provides a sodium ion battery, comprising a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode is the sodium zinc aluminum nickel manganese oxide layered oxide or the sodium zinc aluminum nickel manganese oxide layered oxide prepared by the preparation method.

[0022] Preferably, the material of the negative electrode is one or both of metallic sodium and hard carbon, and the electrolyte is a mixture of ethylene carbonate:propylene carbonate and 5% fluoroethylene carbonate in a volume ratio of 1:1, ethylene carbonate in a volume ratio of 1:1:1, a mixture of propylene carbonate, fluoroethylene carbonate and 5% fluoroethylene carbonate, or a mixture of propylene carbonate and fluoroethylene carbonate in a volume ratio of (95:5) to (98:2).

[0023] Preferably, the sodium ion battery is a soft pack battery or a button battery.

[0024] The present application provides a sodium zinc aluminum nickel manganese oxide layered oxide, the molecular formula of which is Na 0.70~ 0.72 Zn 0.05 Al 0.05 Ni 0.28 Mn 0.62 O2, which is a P2 pure phase sodium ion layered oxide, and by simultaneously introducing metal elements Zn, Al, Ni and Mn, which form bonds with O, sodium atoms are distributed between the composite oxide layers formed by the above metal elements and oxygen elements, which is beneficial to improving the structural stability of the sodium zinc aluminum nickel manganese oxygen layered oxide. At the same time, the layered oxide provided in the present application has stable large current cycling performance and good rate performance as a positive electrode material for a sodium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is a schematic diagram of the structure of the sodium-zinc-aluminum-nickel-manganese-oxygen layered oxide positive electrode material of the present invention;

[0026] Figure 2 This is a spherical aberration electron microscope photograph of the zinc-aluminum-nickel-manganese-oxygen layered oxide positive electrode material prepared in Example 1 of the present invention;

[0027] Figure 3 XRD of the sodium-zinc-aluminum-nickel-manganese-oxygen layered oxide positive electrode material for the sodium-ion battery in Example 1 of the present invention;

[0028] Figure 4 The sodium zinc aluminum nickel manganese oxygen layered oxide positive electrode material of the sodium ion battery in Example 1 of the present invention is 10mAg -1First cycle charge and discharge curve under current density;

[0029] Figure 5 The sodium zinc aluminum nickel manganese oxygen layered oxide positive electrode material of the sodium ion battery in Example 1 of the present invention is 100mAg -1 Cycling performance diagram under current density;

[0030] Figure 6 This is a rate performance diagram of the sodium-zinc-aluminum-nickel-manganese-oxygen layered oxide positive electrode material for a sodium-ion battery in Example 1 of the present invention;

[0031] Figure 7 XRD of the sodium-zinc-aluminum-nickel-manganese-oxygen layered oxide positive electrode material for the sodium-ion battery in Example 2 of the present invention;

[0032] Figure 8 The sodium zinc aluminum nickel manganese oxygen layered oxide positive electrode material of the sodium ion battery in Example 2 of the present invention is 10mAg -1 First cycle charge and discharge curve under current density;

[0033] Fig. 9 The sodium zinc aluminum nickel manganese oxygen layered oxide positive electrode material of the sodium ion battery in Example 2 of the present invention is 100mAg -1 Cycling performance diagram under current density;

[0034] Fig.10 XRD of the sodium-zinc-aluminum-nickel-manganese-oxygen layered oxide positive electrode material for the sodium-ion battery in Example 3 of the present invention;

[0035] Fig.11 The sodium zinc aluminum nickel manganese oxide positive electrode material of the sodium ion battery in Example 3 of the present invention is 10mAg -1 First cycle charge and discharge curve under current density;

[0036] Fig.12 The sodium zinc aluminum nickel manganese oxide positive electrode material of the sodium ion battery in Example 3 of the present invention is 100mAg -1 Cycling performance diagram under current density;

[0037] Fig.13 The sodium-zinc-aluminum-nickel-manganese-oxygen layered oxide positive electrode material of the sodium-ion battery in Example 4 of the present invention is 1000 mAg in the sodium-ion full battery -1 Cycling performance diagram under current density;

[0038] Fig.14 XRD of the sodium-zinc-aluminum-nickel-manganese-oxygen layered oxide positive electrode material for sodium-ion batteries prepared in Comparative Example 1;

[0039] Fig.15 This is the XRD of the sodium-zinc-aluminum-nickel-manganese-oxygen layered oxide positive electrode material for sodium-ion batteries prepared in Comparative Example 2. DETAILED DESCRIPTION

[0040] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.

[0041] In view of the poor structural stability of sodium-nickel-manganese-oxygen layered oxides in the prior art and the performance requirements for improving the performance of positive electrode materials, the present application provides a sodium-zinc-aluminum-nickel-manganese-oxygen layered oxide, which improves the structural stability of the nickel-zinc-aluminum-nickel-manganese-oxygen layered oxide by introducing different proportions of sodium, zinc, aluminum, nickel, and manganese to form a pure-phase layered structure, and as a positive electrode material for sodium ion batteries, the sodium ion batteries have better cycle performance and rate performance. Specifically, the embodiment of the present invention discloses a sodium-zinc-aluminum-nickel-manganese-oxygen layered oxide as shown in formula (I),

[0042] Na 0.70~0.72 Zn 0.05 Al 0.05 Ni 0.28 Mn 0.62 O2 (Ⅰ).

[0043] The schematic diagram of the structure of the sodium zinc aluminum nickel manganese oxygen layered oxide of the present application is as follows Figure 1 As shown, specifically: the layered oxide is composed of several layers of composite oxide and sodium atoms, and the sodium atoms are distributed between two layers of composite oxide; oxygen in the composite oxide is bonded to zinc, aluminum, manganese and nickel, and oxygen atoms are distributed on the surface of the zinc, aluminum, manganese and nickel.

[0044] In the sodium zinc aluminum nickel manganese oxygen layered oxide provided in the present application, zinc atoms, aluminum atoms, manganese atoms and nickel atoms are bonded with oxygen atoms, and the oxygen atoms are formed on the surface of the above atoms, thereby forming a composite oxide composed of zinc aluminum nickel manganese oxygen, and multiple sodium atoms are distributed between the two layers of composite oxides. Repeating the above structure composition will obtain a sodium zinc aluminum nickel manganese oxygen layered oxide. Specifically, the molecular formula of the sodium zinc aluminum nickel manganese layered oxide is Na 0.70 Zn 0.05 Al 0.05 Ni 0.28 Mn 0.62 O2、Na 0.71 Zn 0.05 Al 0.05 Ni 0.28 Mn 0.62 O2、Na 0.72 Zn 0.05 Al 0.05 Ni 0.28 Mn 0.62 O2.

[0045] The size of the sodium zinc aluminum nickel manganese oxide layer described in the present application is 3 to 5 μm.

[0046] The present application also provides a method for preparing sodium zinc aluminum nickel manganese oxygen layered oxide, comprising the following steps:

[0047] S1) mixing a sodium source compound, a zinc source compound, an aluminum source compound, a manganese source compound, and a nickel source compound with a chelating agent according to a ratio to obtain a mixed solution;

[0048] S2) heating the mixed solution until a gel is formed;

[0049] S3) sintering the gel at 100-200° C., 400-600° C. and ≥950° C. in sequence to obtain sodium zinc aluminum nickel manganese oxygen layered oxide.

[0050] In the preparation process of sodium zinc aluminum nickel manganese oxide layered oxide, firstly, sodium source compound, zinc source compound, aluminum source compound, manganese source compound, nickel source compound are mixed with chelating agent according to the ratio to obtain a mixed solution; in this process, the sodium source compound, the zinc source compound, the aluminum source compound, the manganese source compound and the nickel source compound are well-known choices for those skilled in the art, for example, the sodium source compound is selected from at least one of sodium nitrate and sodium acetate; the zinc source compound is selected from at least one of zinc nitrate and zinc acetate; the aluminum source compound is selected from aluminum nitrate; the manganese source compound is selected from at least one of manganese nitrate and manganese acetate; the nickel source compound is selected from at least one of nickel nitrate and nickel acetate; further, the sodium source compound is selected from sodium acetate, the zinc source compound is selected from zinc acetate, the manganese source compound is selected from manganese acetate, and the nickel source compound is selected from nickel acetate. The chelating agent can be specifically selected from citric acid monohydrate. The molar ratio of the sodium source compound, the zinc source compound, the aluminum source compound, the nickel source compound, the manganese source compound and the chelating agent is (0.72-0.75): 0.05: 0.05: 0.28: 0.62: 2.26; specifically, the molar ratio of the sodium source compound, the zinc source compound, the aluminum source compound, the nickel source compound, the manganese source compound and the chelating agent is 0.72: 0.05: 0.05: 0.28: 0.62: 2.26, 0.73:0.05:0.05:0.28:0.62:2.26, 0.74:0.05:0.05:0.28:0.62:2.26 or 0.75:0.05:0.05:0.28:0.62:2.26; if the sodium source compound, zinc source compound, aluminum source compound, nickel source compound and manganese source compound are not within the above molar range, pure phase sodium zinc aluminum nickel manganese oxygen layered oxide cannot be formed. The above mixing is preferably carried out in a glove box, wherein the content of water and oxygen is less than 0.1ppm.

[0051] The present application then heats the mixed solution to form a gel; the heating is preferably performed in a water bath environment, the temperature of the water bath environment is 50-100°C, specifically, the temperature of the water bath environment is 60-80°C.

[0052] According to the present invention, the gel is finally sintered at 100-200°C, 400-600°C and ≥950°C in sequence to obtain sodium zinc aluminum nickel manganese oxide layered oxide; the above sintering is carried out in stages, the sintering at 100-200°C is to remove the moisture in the gel, the sintering at 400-600°C is to remove the C in the gel, and the sintering at ≥950°C is to form a pure phase layered oxide. Specifically, the sintering temperatures are 130-180°C, 420-480°C, 950-1100°C in sequence; the sintering times are 5-10h, 5-10h or 10-15h respectively; for example, the sintering temperatures are 150°C, 500°C and 950°C in sequence, and the corresponding sintering times are 6h, 6h or 12h in sequence.

[0053] The present application also provides a sodium ion battery, comprising a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode is the sodium zinc aluminum nickel manganese oxygen layered oxide described in the above scheme.

[0054] In the sodium ion battery, the negative electrode and the electrolyte are both types well known to those skilled in the art, and there is no particular limitation in this application; in a specific embodiment, the material of the negative electrode is one or both of metallic sodium and hard carbon, and the electrolyte is a mixture of ethylene carbonate: propylene carbonate and 5% fluoroethylene carbonate in a volume ratio of 1:1, ethylene carbonate in a volume ratio of 1:1:1, a mixture of propylene carbonate and fluoroethylene carbonate and 5% fluoroethylene carbonate, or a mixture of propylene carbonate and fluoroethylene carbonate in a volume ratio of (95:5) to (98:2); the above 5% fluoroethylene carbonate represents the volume percentage of fluoroethylene carbonate in the mixture. There is no particular limitation on the type of the sodium ion battery, which can be a soft pack battery or a button battery, and there is no particular limitation in this application.

[0055] In order to further understand the present invention, the sodium zinc aluminum nickel manganese oxide layer provided by the present invention, its preparation method and application are described in detail below in conjunction with the examples. The protection scope of the present invention is not limited by the following examples.

[0056] Example 1

[0057] 13.56mmol citric acid monohydrate, 4.39mmol sodium acetate, 1.7mmol nickel acetate, 3.7mmol manganese acetate, 0.3mmol zinc acetate, 0.3mmol aluminum nitrate were dissolved in 25ml deionized water and stirred evenly to form solution A; solution A was stirred in a 70℃ water bath environment until evaporated to form gel A; gel A was ground and sintered at 150℃, 500℃ and 950℃ in turn, and the reaction time was 360min, 360min and 720min respectively, to obtain a finished powder, namely Na 0.70 Zn 0.05 Al 0.05 Ni 0.28 Mn 0.62 O2 sodium zinc aluminum nickel manganese oxygen layered oxide.

[0058] Figure 2 This is a spherical aberration electron microscope image of the finished powder prepared in this embodiment. It can be seen from the image that the metal atoms in the finished powder prepared in this embodiment are distributed in layers.

[0059] Figure 3 This is the XRD diagram of the finished powder prepared in this example. It can be seen from the figure that the product prepared in this example is a pure phase P2 sodium ion layered oxide.

[0060] Preparation of positive electrode sheet: The sodium zinc aluminum nickel manganese oxide layered oxide prepared in Example 1, conductive carbon black, and binder polyvinylidene fluoride were mixed in a mass ratio of 7:2:1, wherein polyvinylidene fluoride was dissolved in NMP with a mass fraction of 5%. After mixing evenly, the mixture was coated on a carbon-coated aluminum foil with a scraper to a film thickness of 150 μm. The film was vacuum dried at 120°C for 10 hours to prepare an electrode sheet with a diameter of 10 mm. The mass of active material loaded on the electrode sheet was 2 mg cm -2 ;

[0061] Battery assembly: In a glove box protected by argon atmosphere, a button cell model CR2032 was assembled with a sodium metal sheet as the negative electrode, Whatman glass fiber as the separator, 1 mol / L sodium perchlorate as the electrolyte, and a mixture of propylene carbonate (PC) and fluoroethylene carbonate (FEC) in a volume ratio of 95:5 as the solvent.

[0062] Battery test: Place the assembled battery at room temperature for testing, test voltage range: 2.5-4.3V.

[0063] The above-obtained batteries were tested, and the specific results were:

[0064] like Figure 4 As shown, Figure 4 The first cycle charge-discharge curve of the sodium-zinc-aluminum-nickel-manganese-oxygen layered oxide positive electrode material synthesized in Example 1. As can be seen from the figure, at 10 mA g-1 The first discharge capacity at the current density is 127.3 mAh g -1 , the first coulombic efficiency is 90.0%.

[0065] like Figure 5 As shown, Figure 5 The sodium zinc aluminum nickel manganese oxide positive electrode material synthesized in Example 1 was heated to 100 mAg -1 The cycling performance at the current density is given by Figure 5 It can be seen that at 100mA g -1 The discharge capacity of the battery increased from 113.3 mAh g to 100 mAh g under the current density. -1 Up to 100.1mAh g -1 , the capacity retention rate is 88.5%.

[0066] like Figure 6 As shown, Figure 6 The rate performance of the sodium zinc aluminum nickel manganese oxide positive electrode material synthesized in Example 1 is shown in the figure. -1 The discharge capacity at the current density is 115.6 mAh g -1 ; 100mA g -1 The discharge capacity at the current density is 110.5 mAh g -1 ; 200mA g -1 The discharge capacity at the current density is 104.0 mAh g -1 ; 300mA g -1 The discharge capacity at the current density is 99.5 mAh g -1 ; 500mA g -1 The discharge capacity at the current density is 92.7 mAh g -1 , 800mA g -1 The discharge capacity at the current density is 84.3 mAh g -1 ; 1000mA g -1 The discharge capacity at the current density is 79.4 mAh g -1 ; 1500mA g -1 The discharge capacity at the current density is 72.5 mAh g -1 ; 2000mA g -1 The discharge capacity at the current density is 64.3 mAh g -1 .

[0067] Example 2

[0068] 13.56mmol citric acid monohydrate, 4.43mmol sodium acetate, 1.7mmol nickel acetate, 3.7mmol manganese acetate, 0.3mmol zinc acetate, 0.3mmol aluminum nitrate were dissolved in 25ml deionized water and stirred evenly to form solution A; solution A was stirred in a 70℃ water bath environment until evaporated to form gel A; gel A was ground and sintered at 150℃, 500℃ and 950℃ in turn, and the reaction time was 360min, 360min and 720min respectively, to obtain a finished powder, namely Na 0.71 Zn 0.05 Al 0.05 Ni 0.28 Mn 0.62 O2 sodium zinc aluminum nickel manganese oxygen layered oxide.

[0069] The obtained product was tested by XRD to be a pure phase P2 layered oxide positive electrode material, such as Figure 7 shown.

[0070] Preparation of positive electrode sheet: The sodium zinc aluminum nickel manganese oxide layered oxide prepared in Example 2, conductive carbon black, and binder polyvinylidene fluoride were mixed in a mass ratio of 7:2:1, wherein polyvinylidene fluoride was dissolved in NMP with a mass fraction of 5%. After mixing evenly, the mixture was coated on a carbon-coated aluminum foil with a scraper to a film thickness of 150 μm. The film was vacuum dried at 120°C for 10 hours to prepare an electrode sheet with a diameter of 10 mm. The mass of active material loaded on the electrode sheet was 2 mg cm -2 ;

[0071] Battery assembly: In a glove box protected by argon atmosphere, a button cell model CR2032 was assembled with a sodium metal sheet as the negative electrode, Whatman glass fiber as the separator, 1 mol / L sodium perchlorate as the electrolyte, and a mixture of propylene carbonate (PC) and fluoroethylene carbonate (FEC) in a volume ratio of 95:5 as the solvent.

[0072] Battery test: Place the assembled battery at room temperature for testing, test voltage range: 2.5-4.3V.

[0073] The above-obtained batteries were tested, and the specific results were:

[0074] like Figure 8 As shown, Figure 8 The first cycle charge-discharge curve of the sodium-zinc-aluminum-nickel-manganese-oxygen layered oxide positive electrode material synthesized in Example 2 is shown in the figure. -1 The first discharge capacity at the current density is 127.9 mAh g -1 , the first Coulombic efficiency is 94.2%.

[0075] like Fig. 9 As shown, Fig. 9 The sodium zinc aluminum nickel manganese oxide positive electrode material synthesized in Example 2 was heated to 100 mAg -1 The cycling performance under current density is shown in the figure. At 100mAg -1 The discharge capacity of the battery increased from 112.4 mAh g to 100 cycles at a current density of -1 Up to 102.5mAh g -1 , the capacity retention rate is 91.2%.

[0076] Example 3

[0077] 13.56mmol citric acid monohydrate, 4.47mmol sodium acetate, 1.7mmol nickel acetate, 3.7mmol manganese acetate, 0.3mmol zinc acetate, 0.3mmol aluminum nitrate were dissolved in 25ml deionized water and stirred evenly to form solution A; solution A was stirred in a 70℃ water bath environment until evaporated to form gel A; gel A was ground and sintered at 150℃, 500℃ and 950℃ in turn, and the reaction time was 360min, 360min and 720min respectively, to obtain a finished powder, namely Na 0.72 Zn 0.05 Al 0.05 Ni 0.28 Mn 0.62 O2 sodium zinc aluminum nickel manganese oxygen layered oxide.

[0078] The obtained product was tested by XRD to be a pure phase P2 layered oxide positive electrode material, such as Fig.10 shown.

[0079] Preparation of positive electrode sheet: The sodium zinc aluminum nickel manganese oxide layered oxide prepared in Example 3, conductive carbon black, and binder polyvinylidene fluoride were mixed in a mass ratio of 7:2:1, wherein polyvinylidene fluoride was dissolved in NMP with a mass fraction of 5%. After mixing evenly, the mixture was coated on a carbon-coated aluminum foil with a scraper to a film thickness of 150 μm. The film was vacuum dried at 120°C for 10 hours to prepare an electrode sheet with a diameter of 10 mm. The mass of active material loaded on the electrode sheet was 2 mg cm -2 ;

[0080] Battery assembly: In a glove box protected by argon atmosphere, a button cell model CR2032 was assembled with a sodium metal sheet as the negative electrode, Whatman glass fiber as the separator, 1 mol / L sodium perchlorate as the electrolyte, and a mixture of propylene carbonate (PC) and fluoroethylene carbonate (FEC) in a volume ratio of 95:5 as the solvent.

[0081] Battery test: Place the assembled battery at room temperature for testing, test voltage range: 2.5-4.3V.

[0082] The above-obtained batteries were tested, and the specific results were:

[0083] like Fig.11 As shown, Fig.11 The first cycle charge-discharge curve of the sodium-zinc-aluminum-nickel-manganese-oxygen layered oxide positive electrode material synthesized in Example 3. As can be seen from the figure, at 10 mA g -1 The first discharge capacity at the current density is 127.1 mAh g -1 , the first coulombic efficiency is 94.6%.

[0084] like Fig.12 As shown, Fig.12 The sodium zinc aluminum nickel manganese oxide positive electrode material synthesized in Example 3 was 100 mAg -1 The cycling performance under current density is shown in the figure. At 100 mA g -1 The discharge capacity of the battery increased from 111.4 mAh g to 111.4 mAh g after 300 cycles of current density. -1 Up to 100.0mAh g -1 , the capacity retention rate is 90.0%.

[0085] Example 4

[0086] 13.56mmol citric acid monohydrate, 4.52mmol sodium acetate, 1.7mmol nickel acetate, 3.7mmol manganese acetate, 0.3mmol zinc acetate, 0.3mmol aluminum nitrate were dissolved in 25ml deionized water and stirred evenly to form solution A; solution A was stirred in a 70℃ water bath environment until evaporated to form gel A; gel A was ground and sintered at 150℃, 500℃ and 950℃ in turn, and the reaction time was 360min, 360min and 720min respectively, to obtain a finished powder, namely Na 0.72 Zn 0.05 Al 0.05 Ni 0.28 Mn 0.62 O2 sodium zinc aluminum nickel manganese oxygen layered oxide.

[0087] The layered oxide prepared above was used as the positive electrode material in a button cell and matched with the hard carbon negative electrode material to form a full cell. Its performance was tested and the results are as follows:

[0088] like Fig.13 As shown, Fig.13 The figure shows the cycle performance of the soft-pack battery of the sodium-zinc-aluminum-nickel-manganese-oxygen layered oxide positive electrode material synthesized in Example 4 at a 2C rate. As can be seen from the figure, the discharge capacity increases from 1.14Ah to 1.01Ah after 100 cycles at a 2C rate, and the capacity retention rate is 88.6%.

[0089] Comparative Example 1

[0090] The preparation method is the same as that in Example 1, except that the amount of aluminum nitrate added is 1.8 mmol.

[0091] The obtained product was tested by XRD. Fig.14 As shown in the figure, it can be seen that the oxide prepared in this comparative example is not a pure phase structure.

[0092] Comparative Example 2

[0093] The preparation method is the same as that in Example 1, except that during the sintering process, the last sintering temperature is 900°C.

[0094] The obtained product was tested by XRD. Fig.15 As shown in the figure, it can be seen that the oxide prepared in this comparative example is not a pure phase structure.

[0095] The above embodiments are only used to help understand the method and core idea of ​​the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

[0096] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A sodium zinc aluminum nickel manganese oxide layered oxide as shown in formula (I), On 0.70~0.72 Zn 0.05 Al 0.05 No 0.28 Mn 0.62 O2(Ⅰ)。 2. The sodium-zinc-aluminum-nickel-manganese-oxygen layered oxide according to claim 1, characterized in that The layered oxide is composed of several layers of composite oxide and sodium atoms, and the sodium atoms are distributed between two layers of composite oxide; oxygen in the composite oxide forms a bond with zinc, aluminum, manganese and nickel, and oxygen atoms are distributed on the surface of the zinc, aluminum, manganese and nickel.

3. The layered oxide according to claim 1, characterized in that The size of the layered oxide is 3 to 5 μm.

4. The method for preparing the sodium-zinc-aluminum-nickel-manganese-oxygen layered oxide according to claim 1 comprises the following steps: S1) mixing a sodium source compound, a zinc source compound, an aluminum source compound, a manganese source compound, and a nickel source compound with a chelating agent according to a ratio to obtain a mixed solution; S2) heating the mixed solution until a gel is formed; S3) sintering the gel at 100-200° C., 400-600° C. and ≥950° C. in sequence to obtain sodium zinc aluminum nickel manganese oxygen layered oxide.

5. The preparation method according to claim 4, characterized in that: The sodium source compound is selected from at least one of sodium nitrate and sodium acetate; the zinc source compound is selected from at least one of zinc nitrate and zinc acetate; the aluminum source compound is selected from aluminum nitrate; the manganese source compound is selected from at least one of manganese nitrate and manganese acetate; the nickel source compound is selected from at least one of nickel nitrate and nickel acetate; and the chelating agent is selected from citric acid monohydrate.

6. The preparation method according to claim 4, characterized in that: The molar ratio of the sodium source compound, the zinc source compound, the aluminum source compound, the nickel source compound, the manganese source compound and the chelating agent is (0.72-0.75): 0.05: 0.05: 0.28: 0.62: 2.

26.

7. The preparation method according to claim 4, characterized in that: The sintering temperatures are 130-180° C., 420-480° C., and 950-1100° C. in sequence; and the sintering times are 5-10 hours, 5-10 hours, or 10-15 hours in sequence.

8. A sodium ion battery comprising a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode is the sodium zinc aluminum nickel manganese oxide layered oxide according to any one of claims 1 to 3 or the sodium zinc aluminum nickel manganese oxide layered oxide prepared by the preparation method according to any one of claims 4 to 7.

9. The sodium ion battery according to claim 8, characterized in that: The material of the negative electrode is one or both of metallic sodium and hard carbon, and the electrolyte is a mixture of ethylene carbonate:propylene carbonate and 5% fluoroethylene carbonate in a volume ratio of 1:1, ethylene carbonate in a volume ratio of 1:1:1, a mixture of propylene carbonate, fluoroethylene carbonate and 5% fluoroethylene carbonate, or a mixture of propylene carbonate and fluoroethylene carbonate in a volume ratio of (95:5) to (98:2).

10. The sodium ion battery according to claim 8, characterized in that: The sodium ion battery is a soft pack battery or a button battery.

Citation Information

Patent Citations

  • Layered oxide positive electrode, preparation method and application thereof and sodium-ion battery containing layered oxide positive electrode

    CN111564605A

  • Sodium-ion battery multi-element positive electrode material and preparation method thereof

    CN111697210A

  • Zinc-doped and zinc-oxide-coated manganese-based layered oxide material as well as preparation method and application thereof

    CN114613981A

  • P2 type layered metal oxide sodium ion battery positive electrode material and preparation method thereof

    CN115394988A

  • Multi-metal co-regulated layered oxide sodium-ion battery positive electrode material as well as preparation method and application thereof

    CN115939369A